Efficacy and safety of eight types Salvia miltiorrhiza injections in the treatment of unstable angina pectoris: A network meta-analysis - Li, Mingxuan; Li, Hongdian; Liu, Hongxu; Lai, Xiaolei; Xing, Wenlong (Frontiers in Pharmacology, 2022)
Background:Salvia miltiorrhiza Bunge. [Lamiaceae, danshen] injection classes (SMIC) is widely used in the treatment of unstable angina (UA). However, it is uncertain which SMIC is more effective in terms of UA efficacy. The purpose of this Network Meta-analysis (NMA) was to compare the treatment effects of various SMIC to determine the best SMIC for the treatment of UA. Methods: The China National Knowledge Infrastructure (CNKI), Wanfang Database, China Science and Technology Journal Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, Web of Science, and Cochrane Library databases were searched to screen randomized controlled trials (RCTs) of SMIC for UA. The search time frame was all from the establishment of the database to May 2022. RevMan 5.3 and Stata 14.0 software were used for NMA. Results: A total of 148 studies including 14,979 patients, including 7,584 cases in the experimental group and 7,395 cases in the control group were included, and eight SMIC were extracted, namely:Danshen injection, Fufang Danshen injection, Guanxinning injection, Danshenchuanxiongqin injection, Danhong injection, Danshentong IIA Huangsuanna injection, Shenxiong Putaotang injection, and Danshenduofensuanyan injection. The results of NMA showed that, in terms of total effective rate, Shenxiong Putaotang injection and Danshenchuanxiongqin injection have the advantage; In terms of ECG efficiency, Danshentong IIA Huangsuanna injection and Danshen injection have an advantage; Danshenchuanxiongqin injection and Danshenduofensuanyan injection were more effective than other SMIC in improving angina pectoris attacks; Shenxiong Putaotang injection has an advantage in improving hs-CRP; Shenxiong Putaotang injection and Danshentong IIA Huangsuanna injection have advantages in improving TC and TG, respectively. Conclusion: The eight SMIC included in the current study were effective in treating UA, Shenxiong Putaotang injection and Danshentong IIA Huangsuanna injection were both superior in improving all outcome indicators. However, there is still a need for larger samples and high-quality randomized controlled trials for more refined comparisons of various SMIC. Systematic Review Registration: [PROSPERO], identifier [CRD42022350872]